2010
DOI: 10.1073/pnas.1001494107
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila behavioral mutant, down and out ( dao ), is defective in an essential regulator of Erg potassium channels

Abstract: To signal properly, excitable cells must establish and maintain the correct balance of various types of ion channels that increase or decrease membrane excitability. The mechanisms by which this balance is regulated remain largely unknown. Here, we describe a regulatory mechanism uncovered by a Drosophila behavioral mutant, down and out ( dao ). At elevated temperatures, dao loss-of-function mutants exhibit seizures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…6A) 64 . Channels produced by sei expression in Xenopus oocytes lack the I Kr -like rectification of mammalian ERG channels and have fast deactivation, much like EAG channels 65 . Bioinformatics and functional analysis comparing Drosophila, C. elegans and sea anemone orthologs indicate the PAS domain sequence was present in an ancestral gene predating the divergence of the bilaterians and cnidarians, but degenerated at least twice during evolution 66 .…”
Section: Kcnh Channels Lacking Pas Domainsmentioning
confidence: 99%
“…6A) 64 . Channels produced by sei expression in Xenopus oocytes lack the I Kr -like rectification of mammalian ERG channels and have fast deactivation, much like EAG channels 65 . Bioinformatics and functional analysis comparing Drosophila, C. elegans and sea anemone orthologs indicate the PAS domain sequence was present in an ancestral gene predating the divergence of the bilaterians and cnidarians, but degenerated at least twice during evolution 66 .…”
Section: Kcnh Channels Lacking Pas Domainsmentioning
confidence: 99%
“…DmErg channels require coexpression with the cytosolic protein down and out (DAO) for plasma membrane trafficking (18). DAO is unique to Drosophila, but it contains a tetratricopeptide repeat (TPR domain), which is a widespread protein interaction motif (18). A TPR-containing protein has also been implicated in HsErg1 trafficking (24).…”
Section: Our First Expression Of Ceerg Inmentioning
confidence: 99%
“…We reasoned that absence of functional expression could be due to impaired trafficking of channels to the plasma membrane. DmErg channels require coexpression with the cytosolic protein down and out (DAO) for plasma membrane trafficking (18). DAO is unique to Drosophila, but it contains a tetratricopeptide repeat (TPR domain), which is a widespread protein interaction motif (18).…”
Section: Our First Expression Of Ceerg Inmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that hERG potassium channels play a role in spike-frequency adaptation (Chiesa et al 1997). hERG-type potassium channels have also been found in Drosophila (Fergestad et al 2010), although it is not clear whether they are present in mechanosensory neurons, in particular.…”
Section: Discussionmentioning
confidence: 97%